The Role of Microbiota on the Incidence of Obesity - Azzahra, Jihan; Bamahry, Aryanti R; Adnan, Endy (Newinera Publisher, 2024)
Obesity is predicted to become a global public health problem, especially in developing countries. Obesity is characterized by a body mass index (BMI) of 30 or more, which is calculated by dividing a person's weight by the square of their height (in kilograms per square meter). The incidence of obesity by age increased from 4.6% in 1980 to 14.0% in 2019. According to the World Health Organization (WHO), around 2 billion adults are classified as overweight, while another 650 million people are categorized as obese. Based on a national survey, the obesity rate in Indonesia is 23.1%, while in South Sulawesi province it is 31.6% (Riskesdas, 2018). This can alter the gut microbiota structurally and functionally, and the gut microbiota can also modulate nutritional status. A certain abundance and diversity of bacteria may facilitate energy storage and metabolic pathways that lead to obesity. Dietary interventions with probiotics, prebiotics, or synbiotics may be effective in counteracting the disturbances observed in the gut microbiota during obesity or unbalanced diets, as they may be able to reduce and maintain body weight. Intestinal anaerobic bacteria, including Firmicute and bacteroids, can hydrolyze carbohydrates that cannot be digested by the intestine, obtaining short chain fatty acids (SCFA) including acetate, propionate and butyrate, which have an impact on human health. Therefore, anaerobic bacteria can inhibit obesity.